Two new species of the ant-eating spider genus Tropizodium Jocqué & Churchill, 2005 (Araneae, Zodariidae, Zodariinae) from India - Prajapati, Dhruv A.; Murthappa, Prashanthakumara S.; Sankaran, Pradeep M.; Sebastian, Pothalil A. (Zootaxa, 2016)
Two new species, Tropizodium kalami sp. n. and Tropizodium viridurbium sp. n. from the genus Tropizodium are described from India. Detailed morphological descriptions, diagnostic features and illustrations of copulatory organs are given. Distribution of both the new species is mapped.